The making of women entrepreneurs in Hong Kong - Chu, Priscilla Pue Ho (Book collections on Project MUSE., 2004)
This book provides a detailed account of Chinese industrial entrepreneurs, and describes and explains the phenomena of women entrepreneurship in Hong Kong. It addresses two main issues: first, the characteristics of Chinese entrepreneurship and women entrepreneurs; second, the factors that constitute the making of Chinese women entrepreneurs in Hong Kong.